Q: What is -17 in parenthesis equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

If you mean: y = 3(-3/2)2+9(-3/2)-8 Then: y = -59/4 or as -14.75

(x+8)(x-1)=0 x+8=0 x=-8 x-1=0 x=1 Therefore, the zeroes are -8 and 1.

4x -17 equals 3 4x equals 20 x equals 5

13/21 - 7/21 = 6/21 Sorry, DJ, 4 over 7 = 12/21 so answer is 5/21

If you're talking about (K-0)=1, then the answer is most definitely 1.

Related questions

There is no operator given an in such cases it is often taken to be multiplication eg ab = a*b Thus 2*(-4)*(3) = -24

7a=2(-10)........................................answer is 20/7

If you mean: y = 3(-3/2)2+9(-3/2)-8 Then: y = -59/4 or as -14.75

No property. Unless n is known there is no property exhibited.

x squared plus 9x plus 20.

its a math problem

(x+8)(x-1)=0 x+8=0 x=-8 x-1=0 x=1 Therefore, the zeroes are -8 and 1.

-(-38 + 17) = 38 + (-17) On the left side we read: the opposite of the quantity. Since that quantity contains two terms, it also means the opposite of both terms. Let me rewrite the left side, such as - {-(38) + [- (-17)]}. (notice, -38 is the opposite of 38, and -(-17) is the opposite of -17) Let me distribute the negative sign to both terms of the quantity, -(-38) + {-[- (-17)]}. So we have an equivalent statement such as -(-38) + {- [-(-17)]} = 38 + (-17) As you see, in this new statement we have the opposite of the opposite of a number which would give us back the number itself, and as a result 38 + (-17) = 38 + (-17) Therefore, the original statement is an identity.

6/2(2+1) =1 In order of operations you do parenthesis first, so it becomes 6/2(3) Then, to eliminate the parenthesis completely, you multiply 2 by 3 and get: 6/6 which equals 1

4g-17 equals = -13

eyess like in a smiley face an equal sign is the eyes and a parenthesis is the smile ex:: =]

2n2y2(2n3)(3y3)